2013
DOI: 10.1089/jamp.2011.0921
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Enhanced Deposition Due to Magnetic Field Alignment of Ellipsoidal Particles in a Lung Bifurcation

Abstract: Results indicate that externally forcing local alignment of high aspect ratio particles can increase local deposition considerably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The experimental results were found to be in good agreement with the CFD simulation data. In another study, Martinez et al [ 224 ] developed a CFD model to study drug delivery through deep down airways by ellipsoidal magnetic particles, where the results showed that the presence of the magnetic increases local enhancement in drug delivery by a factor of 1.43–3.46 in symmetrical bronchial bifurcation. Pourmehran et al [ 225 ] presented a CFD model of a realistic lung model (G0-G2) to investigate deposition efficiency under the influence of non-uniform magnetic field.…”
Section: Magnetic Drug Delivery To Lung Tumors Through the Respiratormentioning
confidence: 99%
“…The experimental results were found to be in good agreement with the CFD simulation data. In another study, Martinez et al [ 224 ] developed a CFD model to study drug delivery through deep down airways by ellipsoidal magnetic particles, where the results showed that the presence of the magnetic increases local enhancement in drug delivery by a factor of 1.43–3.46 in symmetrical bronchial bifurcation. Pourmehran et al [ 225 ] presented a CFD model of a realistic lung model (G0-G2) to investigate deposition efficiency under the influence of non-uniform magnetic field.…”
Section: Magnetic Drug Delivery To Lung Tumors Through the Respiratormentioning
confidence: 99%
“…It has been hypothesized that some of these drawbacks could be alleviated through the incorporation of magnetic agents into the inhalable drugs and thereby control lung deposition using external magnetic fields (Christian, 2008;Longest and Holbrook, 2012;Saadat et al, 2020); a concept that has been extensively explored in silico over the past decade with computational fluid dynamic simulations (Kenjereš and Tjin, 2017;Manshadi et al, 2019;Martinez et al, 2012;Pourmehran et al, 2015). Since the aerodynamic drag forces exerted on airborne inhaled particles are vastly stronger than the magnetic force imposed by magnets, deflecting particles under airflow and depositing them on target has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Pourmhran et al22 simulated magnetic particle deposition in a three-dimensional reconstructed tracheobronchial airway from computed tomography scans. Deeper down the conducting airways, Martinez et al23 simulated the behavior of ellipsoidal magnetic particles in models of symmetrical terminal bronchiole bifurcations.…”
Section: Introductionmentioning
confidence: 99%